Psoriasis Vulgaris Exacerbation during Treatment with a PD-1 Checkpoint Inhibitor: Case Report and Literature Review - De Bock, Marlies; Hulstaert, Eva; Kruse, Vibeke; Brochez, Lieve (Case reports in dermatology, 2018)
Objective: The incidence of immune-related adverse events is growing as the use of checkpoint inhibitors is exponentially increasing. Cutaneous adverse events are among the most frequent immune-related adverse events. The purpose of this case report and literature review is to highlight psoriasis as a potential adverse event with need for early recognition. Case Report and Literature Review: We describe the case of a 65-year-old woman with psoriasis exacerbation while treated with nivolumab (anti-PD-1) for a stage IV melanoma. She had a history of scalp psoriasis but she presented with psoriatic lesions on both lower and upper limbs. Our patient was treated with topical steroids. So far, 34 other cases with an exacerbation of psoriasis during treatment with anti-PDL-1 or PD-1 therapy have been reported in the literature. A broad range of therapies are described, without any available guidelines for this particular condition. Conclusion: Psoriasis exacerbation is an established side effect of PD-1/PDL-1 checkpoint inhibitors with 35 reported cases. Early recognition and management are challenging as there are no clear guidelines available. A close collaboration between oncologist and dermatologist is mandatory to manage this immune-related adverse event.